A case report of COVID-19 infection and management during pregnancy. (May 2021) - Ogamba, Ifeoma; Chuang, Linus; Panarelli, Erin; Zilberman, Dimitry
Coronavirus disease 2019 (COVID-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) which started in Wuhan, Hubei Province, China, and progressed to a pandemic affecting over 210 countries and territories including the United States. The severity of symptoms range from mild to critical disease involving multi-organ failure; however, many pregnant COVID-19 patients have mild symptoms. The understanding of COVID-19 is evolving and there is limited data about its effects in pregnancy. This case series features two pregnant patients with COVID-19 with a range of symptoms, including fever, non-productive cough, headache, and worsening dyspnea. Both patients had chest x-ray findings notable for lung opacities, and lymphopenia was a consistent abnormal laboratory finding. Both of the patients had hypoxia which was treated with hydroxychloroquine and lopinavir-ritonavir with significant improvement in clinical symptoms and prolongation of pregnancy.